O16-3 Seroprevalence of hepatitis B virus and occupational injuries in nursing students during the clinical learning. (1st September 2016) - Spada, Laura; Portoghese, Igor; Noli, Marcello; Mascia, Nicola; Mereu, Noemi Maria; Piazza, Maria Francesca; Coppola, Rosa Cristina; Campagna, Marcello
Abstract : Introduction: Hepatitis B (HBV) represents a main occupational infectious disease. Nursing students (NSs) are a risk group for acquiring HBV occupational infection after accidental contact with blood or body fluids contaminated with the virus. During their everyday clinical learning, they are exposed to needle stick injuries and sharp injuries (NSSIs) probably due to limited experience in handling needles. Objectives: We assessed the risk of HBV infection and NSSIs rate among italian NSs. Methods: We evaluated the seroprevalence of HBV markers in a sample of 247 NSs. We analysed the rate of NSSIs in a sample of 640 third-year students. Results: The 54% of students were anti-HBs positive, 42% were negative, and 4% had a borderline value (10–11 Ul/ml). One student was serologically HBsAg negative and was positive for anti-HBc (IgG). All participants were negative for HBsAG and Anti HCV. Regarding injuries, 43/640 (7%) occurred among NSs. Among these, 37/43 (86.1%) were caused by NSSIs. The most part of NSSIs occurred in wards of Internal Medicine. NSSIs occurred more frequently during the drawing of patients' venous blood (24%) and the most commonly injured body area was the first finger (38%). Discussion: Results from NSSIs, as well as those from non-responders, showed that the incidence of injuries among NSs without immunisation is rare. Nevertheless, in case of injury, the risk to contract HBV can be high. This suggests the importance of serological screening and vaccination against HBV. Furthermore, making NSs clinical learning more effective and safe by improving information, education and training are crucial to better manage the HBV infection risk during their internship. The study was conducted with the support of the Italian Ministry of Health, CCM Program 2013.